2013
DOI: 10.1021/op400228z
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed C–N Coupling in the Synthesis of Integrase Inhibitors of Immunodeficiency Viruses

Abstract: This contribution describes the total synthesis of a complex macrocyclic integrase inhibitor, a key enzyme involved in the infection process of various immunodeficiency viruses. The key transformation of the synthetic strategy was the selective C–N coupling of a sulfonamide to a heteroaryl bromide in the presence of potentially competing amide and carbamate functionalities. The transformation was accomplished with CuI catalysis using bypiridine as the ligand in the presence of base and enabled a convergent app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Further ligand screening which includes 2,2′-bipyridine ( L20 ), 1,10-phenanthroline ( L21 ), l -prolines ( L22 and L23 ), picolinic acid ( L24 ), N -oxide ( L25 ), and oxalic diamides ( L26 and L27 ) demonstrated that L15 is the optimal ligand to our target reaction (entry 11 and Table S2). Then, cyclohexenyl triflate ( 10b ) was subjected to the reaction under the aforementioned conditions (Table S2). In this case, the Cu systems displayed a reversal reactivity toward the ring size of cyclic vinyl triflate, leading to only 41% yield of cyclohexenyl hydrazine 11b in spite of the same reaction conditions described in Table , entry 6.…”
Section: Resultsmentioning
confidence: 99%
“…Further ligand screening which includes 2,2′-bipyridine ( L20 ), 1,10-phenanthroline ( L21 ), l -prolines ( L22 and L23 ), picolinic acid ( L24 ), N -oxide ( L25 ), and oxalic diamides ( L26 and L27 ) demonstrated that L15 is the optimal ligand to our target reaction (entry 11 and Table S2). Then, cyclohexenyl triflate ( 10b ) was subjected to the reaction under the aforementioned conditions (Table S2). In this case, the Cu systems displayed a reversal reactivity toward the ring size of cyclic vinyl triflate, leading to only 41% yield of cyclohexenyl hydrazine 11b in spite of the same reaction conditions described in Table , entry 6.…”
Section: Resultsmentioning
confidence: 99%
“…Ullmann coupling of 333 and 334 was identified as the key transformation in the convergent assembling of this molecule (Scheme 69). 202 Screening of a variety of catalysts, ligands, bases, solvents, and solvents and limited optimization revealed that the conditions of 1.0 equiv of CuI, 0.3 equiv of BPY (L55), and 4.0 equiv of K 2 CO 3 in DMF at 70 °C offered the best yield and site selectivity in the presence of potentially competing reactions from NH−carboxamide and NH− carbamate bonds. Upon reaction completion, the reaction mixture was concentrated to remove the majority of DMF, diluted with THF and water, and acidified with 2 N HCl.…”
Section: Applications In Route Design Process Development and Scale-u...mentioning
confidence: 99%
“…Nach der Testung von Katalysatoren, Liganden und Basen fanden sie heraus, dass die besten Bedingungen der Einsatz von 100 Mol‐% CuI und 100 Mol‐% Bipyridin‐Ligand ( L47 ) sind. Zwar werden große Mengen Kupferiodid benötigt, dieses kann jedoch während der Aufarbeitung mithilfe von EDTA auf das ppm‐Niveau reduziert werden, und im fertigen Wirkstoff ist kein Cu mehr nachweisbar (Schema ) …”
Section: Cu‐katalysierte Kreuzkupplungen Von Arylhalogeniden Mit Nuclunclassified